2012
DOI: 10.1111/j.1747-0080.2012.01631.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal controlling feeding behaviours and child eating in preschool‐aged children

Abstract: Aim: This paper explored the relationship between maternal controlling feeding behaviours and child eating and weight in preschool-aged children. Methods: Ninety mothers of 2-to 5-year-old children (M = 3.48, SD = 0.84, 54.4% males) completed self-report measures assessing maternal controlling feeding behaviours, child eating patterns and weight. Results: Univariate analyses indicated that child food neophobia was associated with authoritarian feeding (r = 0.29), pressure to eat (r = 0.28) and restriction (r =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 49 publications
3
13
0
2
Order By: Relevance
“…Of note, the reluctance to sample new foods (food neophobia) is believed to be a genetic trait linked to an anxious phenotype 27 whereas picky eating is believed to be related to environmental context and parenting. 28,29 Mothers seemed comfortable accepting their child’s reluctance to try new foods in that reluctance was not associated with concern about undereating. Yet, picky eating and a thinner body type were associated with maternal concern about undereating.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the reluctance to sample new foods (food neophobia) is believed to be a genetic trait linked to an anxious phenotype 27 whereas picky eating is believed to be related to environmental context and parenting. 28,29 Mothers seemed comfortable accepting their child’s reluctance to try new foods in that reluctance was not associated with concern about undereating. Yet, picky eating and a thinner body type were associated with maternal concern about undereating.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to 'fixed' predictors, picky eating at 38 months in ALSPAC was associated with a greater maternal age, maternal smoking (yes), higher maternal social class, lower prepregnancy body mass index, higher maternal educational attainment, lower parity, and the infant being of lighter birthweight and male. (2) Other studies, however, have found boys and girls to be equally affected, (23) with the presence of siblings being protective (7) . Several studies have investigated familial similarity for food neophobia (rather than picky eating per se) and found low to moderate similarity, suggesting a moderate degree of heritability.…”
Section: Causes Of Picky Eatingmentioning
confidence: 96%
“…Picky eating appears to affect girls and boys equally (Moroshko & Brennan, 2013), but the presence of siblings seems to be protective against the development of picky eating, as does greater maternal age (Hafstad, Abebe, Torgersen, & von Soest, 2013). Maternal healthy eating behaviour has been associated with lower child food fussiness (Gregory, Paxton, & Brozovic, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…The development of picky eating may be affected by factors such as pressure to eat, personality factors, and parental practices/ feeding styles, including parental control and social influences (Jani Mehta, Mallan, Mihrshahi, Mandalika, & Daniels, 2014;Moroshko & Brennan, 2013), as well as specific factors, such as the absence of exclusive breastfeeding, the introduction of complementary foods before 6 months (Shim, Kim, Mathai, & Team, 2011), and the late introduction of chewy foods (Northstone, Emmett, Nethersole, & ALSPAC Study Team, 2001). Picky eating appears to affect girls and boys equally (Moroshko & Brennan, 2013), but the presence of siblings seems to be protective against the development of picky eating, as does greater maternal age (Hafstad, Abebe, Torgersen, & von Soest, 2013).…”
Section: Introductionmentioning
confidence: 99%